The defect evolution in homoepitaxial AlN layers grown by high-temperature metal–organic chemical vapor deposition. Issue 19 (24th April 2018) - Jiang, Ke; Sun, Xiaojuan; Ben, Jianwei; Jia, Yuping; Liu, Henan; Wang, Yong; Wu, You; Kai, Cuihong; Li, Dabing
Abstract : The defect evolution in homoepitaxial AlN grown by high-temperature metal–organic chemical vapor deposition on AlN/sapphire templates was studied. Abstract : AlN homoepitaxy is a promising way to obtain high-quality AlN and Al-rich AlGaN and thus deep ultraviolet devices. The defect evolution in homoepitaxial AlN grown by high-temperature metal–organic chemical vapor deposition on AlN/sapphire templates was studied here. The schematic defect evolution model was given and the driving force of the dislocation motion was analyzed. Experimental results revealed that the dislocation line deflection angles changed differently for different types of threading dislocation at the interface of the AlN/sapphire template and the epilayer. The interface stress was considered to be the driving force of dislocation motion. The driving force needed for the change of deflection angles followed the sequence of pure screw dislocation > mixed dislocation > pure edge dislocation. The defect density exhibited a strong relationship with the strain states, indicating that the control of interface stress was an effective way to control the quality of homoepitaxial AlN. These results can not only provide deeper understanding of the AlN homoepitaxy mechanism, but also offer a way to grow high-quality AlN.